Board directors' preferences: What are good aggregation rules? - Mihael Duran (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
I analyze how boards of directors with heterogeneous preferences can affect the information shared with the CEO with the help of a cheap-talk model that allows for large groups of receivers. This paper provides new insights on how heterogeneity of boards can change the way of communication between the board and the CEO, related to different ways of decision making. My model gives some insights how heterogeneous preferences can have an impact on how communication between CEO and the board of directors takes place. I also indicate how coalition forming in the boardroom can be influenced by director's and CEO's perferences. Finnaly this model gives a possible answer why board of directors hetreogeneity differs even for shareholder representatives if there are any empoyees on the board.
urn:nbn:de:bsz:21-opus-69045
Keywords: C71; C72; D72; D82; G34; 330; Board of directors; Cheap talk; Director's preferences; Heterogeneity; Multiple audiences